Antimicrobial Activity of Metabolites from Chaetomium to Control Root Rot (Phytophthora parasitica) and Colletotrichum gloeosporioides (anthracnose) in Citrus - Pheaktra Phal; Kasem Soytong; Rujira Tangon; Song Jiaojiao (My University, 2021)
Citrus diseases were studied which found anthracnose caused by Colletotrichum gloeosporioides and root rot caused by Phytophthora parasitica which seriously invaded in Thailand where citrus are grown.The chemical fungicides have been traditionally using by the growers until those chemicals are non-effective control.Chaetomium species are proved to be antagonistic fungi against phytopathogens by using their biopreparation or active metabolites to control those diseases.The purpose of investigation was evaluated active metabolites derived from Chaetomium cupreum and Chaetomium cochliodes to control those pathogens.The phytopathogens were isolated, identified and proved to be pathogenic isolates.The factorial experiments in Completely Randomized Design were conducted to gathered data for statistical analysis.Chaetomium's metabolites were crude hexane, ethyl acetate and hexane extracts that tested to 0, 10, 50, 100, 500 and 1000 ppm.Results showed that crude EtoAC extract of C. cupreum showed the best anifungal activity against C. gloeosporioides with the ED50 of 275 ppm.Moreover, crude MeOH extract derived from C. cochliodes inbibited the sporulation C. gloeosporioides with the ED50 of 532 ppm.However, crude EtoAC extract derived C. cupreum suppressed the production of sporangia of P. parasitica at ED50 of 98 ppm., and crude MeOH extract from C. cochliodes showed the highest sporangia supression of P. parasitica at the ED50 of 44 ppm.Further investigation is being conducted to control those citrus diseases in pot and field trials.
Keywords: Chaetomium; Root rot; Colletotrichum; Phytophthora cactorum; Phytophthora capsici; Chaetomium globosum; Plant Pathogens and Fungal Diseases